The new business is circular? Analysis from the perspective of the circular economy and entrepreneurship - Kuzma,Edson Luis (2021)
Abstract Paper aims The objective of this article is to explore the relationship between circular economy and entrepreneurship, to propose an agenda for future research to advance in the field and generate managerial implications. Originality The study helps to identify the research profile and enable the development of a logical structure for analyzing entrepreneurship carried out in the specific context of companies operating under the guidance of the circular economy. Research method The method is a systematic literature review, peer-reviewed and indexed in ten databases. The research protocol adopted aimed at: i) searching and searching the databases, ii) sorting and selecting the literature, iii) coding and analyzing the data. Main findings The results point to: i) predominance of causation logic in the market environment, ii) attention to the creation of relationship and value networks, iii) entrepreneurship aimed at valorization, iv) focus on innovation in production, regional development and exploitation of market failures. Implications for theory and practice The main contribution of the study is to consolidate the knowledge in the field of circular economy and entrepreneurship, still little explored. The results provide a basis for managers and decision-makers to expand their business and create new models based on the circular economy.